Bulked Segregant RNA Sequencing Revealed Difference Between Virulent and Avirulent Brown Planthoppers - Guan, Wei; Shan, Junhan; Gao, Mingyang; Guo, Jianping; Wu, Di; Zhang, Qian; Wang, Jing; Chen, Rongzhi; Du, Bo; Zhu, Lili; He, Guangcun (Frontiers in Plant Science, 2022)
The brown planthopper (Nilaparvata lugens Stål, BPH) is one of the most devastating insect pests of rice (Oryza sativa L.), but BPH populations have varying degrees of virulence to rice varieties carrying different resistance genes. To help efforts to characterize these variations we applied bulked segregant RNA sequencing (BSR-seq) to identify differentially expressed genes (DEGs) and genetic loci associated with BPH virulence to YHY15 rice plants carrying the resistance gene Bph15. BPHs that are highly virulent or avirulent to these plants were selected from an F2 population to form two contrasting bulks, and BSR-seq identified 751 DEGs between the bulks. Genes associated with carbohydrate, amino acid and nucleotide metabolism, the endocrine system, and signal transduction were upregulated in the avirulent insects when they fed on these plants. The results also indicated that shifts in lipid metabolism and digestive system pathways were crucial for the virulent BPHs’ adaptation to the resistant rice. We identified 24 single-nucleotide polymorphisms (SNPs) in 21 genes linked with BPH virulence. Possible roles of genes apparently linked to BPH virulence are discussed. Our results provide potentially valuable information for further studies of BPH virulence mechanisms and development of robust control strategies.